1999
DOI: 10.1002/pc.10359
|View full text |Cite|
|
Sign up to set email alerts
|

Measurement of principal permeability with the channel flow experiment

Abstract: A framework for channel flow permeability measurement in resin transfer molding (RTM) is developed in this paper. For the channel flow experiment, five possible experimental configurations are identified, of which two have not yet been mentioned in the literature. Starting from effective permeability, the entity measured in the experiment, explicit formulas for principal permeability and its orientation in two and three dimensions are developed. These formulas are applied to (published) experimental results th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 12 publications
0
34
0
Order By: Relevance
“…As discussed by Weitzenböck et al [20], small variations of the effective permeabilities, K eff 0Њ , K eff 45Њ , and K eff 90Њ , cause a noticeable change in the permeability tensor. In fact, it was found that a variation of Ϯ5% in K eff 90Њ (the effective permeability in the weft direction) yields a variation of the predicted angle ␤ of around Ϯ8%.…”
Section: Comparison Of the Iterative Ellipse Methods With Published Datamentioning
confidence: 90%
See 3 more Smart Citations
“…As discussed by Weitzenböck et al [20], small variations of the effective permeabilities, K eff 0Њ , K eff 45Њ , and K eff 90Њ , cause a noticeable change in the permeability tensor. In fact, it was found that a variation of Ϯ5% in K eff 90Њ (the effective permeability in the weft direction) yields a variation of the predicted angle ␤ of around Ϯ8%.…”
Section: Comparison Of the Iterative Ellipse Methods With Published Datamentioning
confidence: 90%
“…Because of the trigonometrical assumptions, this method is only valid if the directions of measurements are taken with an increment of 45°. The iterative ellipse technique proposed here, based on the reconstruction of the permeability ellipse, is more general and different from that of Weitzenböck et al [20].…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…A lot of researches were focused on the measurements of the permeability of glass fibre mats used for resin transfer molding (RTM) applications [20][21][22][23][24][25][26][27][28][29][30][31][32][33]. In this case, Darcy law was used and applied for a Newtonian flow:…”
Section: Permeability Measurements Of Glass Fibre Matsmentioning
confidence: 99%